EFEKTIVITAS PENERAPAN SIASN TERHADAP KUALITAS PELAYANAN ADMINISTRASI KEPEGAWAIAN DI BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA KABUPATEN SUMBAWA BARAT - FAKHRUDDIN, ERWIN; UMAR, UMAR; YULIADI, IMAM (GANEC SWARA, 2023)
The purpose of this research is to describe the implementation of the Civil Servant Information System (SIASN) innovation in improving the quality of administrative personnel services and to analyze the effectiveness of the implementation of the Civil Servant Information System (SIASN) innovation on the quality of administrative personnel services in the Badan Kepegawaian dan Pengembangan Sumber Daya Manusia (BKPSDM) Kabupaten Sumbawa Barat. The research findings show that the implementation of the Civil Servant Information System (SIASN) innovation in the BKPSDM Kabupaten Sumbawa Barat has been successful, resulting in an improvement in the quality of administrative personnel services. This improvement includes increased efficiency, transparency, and accuracy in administrative personnel matters.Regarding the effectiveness of the SIASN implementation at the BKPSDM Kabupaten Sumbawa Barat, it can be evaluated based on the indicators of Easier, Better, Faster, Cheaper, and Safety. In general, the effectiveness is considered "Effective" as the average score from these five indicators is 120, falling within the range of 105 - 129. The relationship/influence can be observed through the correlation value, with an R Square value of 0.688, indicating that 68.8% of the Quality of Administrative Personnel Services is influenced by the Effectiveness of SIASN Implementation.The hypothesis testing using the t-test resulted in a significance value of 0.000, which is less than 0.05. Based on the t-value, which is 7.860 and greater than the t-table value of 2.048, it can be concluded that the Effectiveness of SIASN Implementation (X) has a significant influence on the Quality of Administrative Personnel Services (Y). These results indicate that the proposed hypothesis is accepted, meaning that the effectiveness of SIASN implementation has a positive impact on the quality of administrative personnel services at the BKPSDM Kabupaten Sumbawa Barat